Influence of Shared Memory and Network Topology in the Consensus Dynamics of a Naming Game - Uzun, Thaís G.; Silva-Filho, Reginaldo J. Da; Brust, Matthias R.; Ribeiro, Carlos H. C. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2011: Anais do XXXVIII Seminário Integrado de Software e Hardware, 2011)
In the Naming Game, individuals or agents exchange pairwise local information in order to communicate about objects in a common environment. The goal of the game is to reach a consensus about naming these objects. In this paper we extend the classical naming game with a globally shared memory accessible by all agents. Although the extended naming game is non-deterministic in its word selection, we show that consensus towards a common vocabulary is reached in diverse network topologies. More importantly, we show the qualitative and quantitative influence of the external source of information, i.e. the shared memory, on the consensus dynamics.